INTEREST DEGREE ESTIMATION DEVICE - FUJIMAKI SHINICHI; KUSUNOKI SHINYA; TAKEDA YUSAKU; TAKAMI AKIHIDE (2024)
To estimate a sufficiently accurate interest degree even when detection accuracy of a sight line position of a driver is not high in interest degree estimation means which estimates the interest degree on the basis of the sight line position of the driver of a vehicle.SOLUTION: An interest degree estimation device includes: saliency map generation means 23 which generates a bottom-up saliency map from a visual field image 50 of a driver of a vehicle; visual field image division means 25 which divides the visual field image 50 into multiple divided regions; interest degree index calculation means 31 which calculates an interest degree index on the basis of a representative value of a saliency value in the divided region including the sight line position of the driver; complexity index calculation means 32 which calculates a complexity index expressing complexity of a travel scene; and interest degree estimation means 33 which estimates an interest degree of the driver on the basis of the interest degree index and the complexity index.SELECTED DRAWING: Figure 1 【課題】 車両の運転者の視線位置に基づいて興味関心度を推定する興味関心度推定手段において、運転者の視線位置の検出精度が高くない場合でも、十分に的確な興味関心度の推定を行い得るものを提供する。【解決手段】 興味関心度推定装置において、車両の運転者の視界画像５０からボトムアップサリエンシーマップを生成するサリエンシーマップ生成手段２３と、視界画像５０を複数の分割領域に分割する視界画像分割手段２５と、運転者の視線位置が含まれる分割領域におけるサリエンシー値の代表値に基づいて関心度指数を算出する関心度指数算出手段３１と、走行シーンの複雑さを表す複雑度指数を算出する複雑度指数算出手段３２と、関心度指数と複雑度指数に基づいて運転者の興味関心度を推定する興味関心度推定手段３３を備えた。【選択図】 図１